An Adaptive Block Backstepping Controller For A Quadrotor - Akgun, Onur; Turker, Turker (IEEE, 2018)
An adaptive block backstepping controller is proposed to control the position of a quadrotor with uncertain model parameters. The controller design procedure is provided considering the stability of six blocks involving the states of the model. In each step the stability of the concerned block is shown by means of Lyapunov stability theorem. The viability and the success of the proposed controller are tested through numerical simulations.
Keywords: TRACKING CONTROL; Automation & Control Systems; Computer Science; Engineering